2017
DOI: 10.1590/0370-44672014700220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shear lag coefficienton circular hollow sections with bolted sleeve connections

Abstract: The circular hollow sections (CHS) are being widely employed in steel structures around the world, increasing the development of new researches. This article proposes an innovative connection model for circular hollow sections that facilitates and reduces the assembly cost of hollow section structures. The proposed connection is a tube sleeve, used to splice two tubes, composed of an inner tube with a diameter smaller than the connecting tubes, which is connected to the outer tubes by bolts passing through bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The results indicated that net section efficiencies attained in the tests were much higher than those prescribed by the design specifications. Moreover, recent studies [28,29] have shown that the negative effects developed by the shear lag in slotted end connections to hollow structural sections (HSS) may be negligible if a minimum weld length (Lw) more that the distance between welds (w) is used. As a result, the failure mode in the connections with the ratio of L w /w≥1.0 is mainly section fracture rather than failure in the connection.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that net section efficiencies attained in the tests were much higher than those prescribed by the design specifications. Moreover, recent studies [28,29] have shown that the negative effects developed by the shear lag in slotted end connections to hollow structural sections (HSS) may be negligible if a minimum weld length (Lw) more that the distance between welds (w) is used. As a result, the failure mode in the connections with the ratio of L w /w≥1.0 is mainly section fracture rather than failure in the connection.…”
Section: Introductionmentioning
confidence: 99%
“…This connection is composed of outer tubes connected by an inner tube and bolts. Ini-tially, the sleeve connection was studied for circular hollow sections (CHS) by Amparo (2014), Amparo et al (2015), Roquete et al (2017), Roquete (2018), Oliveira (2019), Oliveira et al (2020), Roquete et al (2021) and Roquete et al (2022). Figure 1 shows an example of sleeve connection with CHS evaluated by Roquete (2018).…”
mentioning
confidence: 99%
“…The shear lag coefficient was also approached by Roquete et al (2017b), who analyzed two bolt configurations: aligned and crossed bolts. Experimental results of 12 prototypes with a variable number of bolts -3, 4 and 5 bolts -, bolt configurations, diameters and thicknesses of the tubes were undertaken, and its shear lag coefficients obtained.…”
mentioning
confidence: 99%